2015
DOI: 10.1007/s00284-015-0841-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of Sophorolipid from an Identified Current Yeast, Lachancea thermotolerans BBMCZ7FA20, Isolated from Honey Bee

Abstract: Biosurfactants are a family of diverse amphipathic molecules that are produced by several microorganisms such as bacteria, molds, and yeasts. These surface active agents have several applications in agriculture, oil processing, food, and pharmaceutical industries. In this research using YMG and YUG culture media, a native yeast strain, HG5, was isolated from honey bee. The oil spread test as a screening method was used to evaluate biosurfactant production by the yeast HG5 isolate. The 5.8s-rDNA analysis confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Other studies confirmed our observation and emphasized that L. thermotolerans is a potent ethanolproducing yeast associated with fruits, fruit jams, and high sugar food (Freel et al 2014). Recently, this species has also been used for production of valuable compounds like sophorolipid surfactants (Mousavi et al 2015). Regarding ethanol resistance, only P. subpelliculosa strains were able to sustain high ethanol, whereas Z. rouxii strains showed a poor tolerance of acidity in the presence 0.5% of acetic acid.…”
Section: Resultssupporting
confidence: 86%
“…Other studies confirmed our observation and emphasized that L. thermotolerans is a potent ethanolproducing yeast associated with fruits, fruit jams, and high sugar food (Freel et al 2014). Recently, this species has also been used for production of valuable compounds like sophorolipid surfactants (Mousavi et al 2015). Regarding ethanol resistance, only P. subpelliculosa strains were able to sustain high ethanol, whereas Z. rouxii strains showed a poor tolerance of acidity in the presence 0.5% of acetic acid.…”
Section: Resultssupporting
confidence: 86%
“…The limitations of the blood haemolysis test are related to difficulties in maintaining the culture conditions in the blood agar media that would favour the production of biosurfactants in addition to possible interference of microbial haemolysins with the results [ 154 ]. Low biosurfactant concentration produced can also present weak diffusion in the solid medium and favour the non-formation of halos [ 25 ].…”
Section: Screening Of Biosurfactant-producing Fungi: Methodologies and Characterizationmentioning
confidence: 99%
“…Low biosurfactant concentration produced can also present weak diffusion in the solid medium and favour the non-formation of halos [ 25 ]. Some results of blood haemolysis tests for fungi and yeasts have been shown to be false-negatives, as they have shown negative results for haemolysis while other positive results are obtained for different tests of surface activity and/or emulsification indexes [ 40 , 67 , 154 ]. Therefore, due to the variability of the results, other screening tests must be associated with blood haemolysis to corroborate biosurfactant production.…”
Section: Screening Of Biosurfactant-producing Fungi: Methodologies and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations